Short-term Impacts of COVID-19 on the Malawian Economy, 2020-21: A SAM multiplier modeling analysis - Baulch, Bob; Botha, Rosemary; Pauw, Karl (2020)
By Bob Baulch, Rosemary Botha and Karl Pauw International Food Policy Research Institute